MANAGEMENT OF EDUCATIONAL PROJECTS IN PRE-UNIVERSITY EDUCATIONAL INSTITUTIONS - Lilia CEBANU; Anca-Mihaela NASTASĂ (Acta et Commentationes, Sciences of Education, 2022)
This article reflects on the management of educational projects in pre-university education institutions. The project concepts, project management, educational project, the stages followed by the project manager and his team, the strategic and tactical conditions as well as the causes of failure / risk in carrying out the projects and the principles of their prevention are described and analyzed.